Biplot and Singular Value Decomposition Macros for Excel© - Lipkovich, Ilya A.; Smith, Eric P. (Journal of Statistical Software, 2002)
The biplot display is a graph of row and column markers obtained from data that forms a twoway table. The markers are calculated from the singular value decomposition of the data matrix. The biplot display may be used with many multivariate methods to display relationships between variables and objects. It is commonly used in ecological applications to plot relationships between species and sites. This paper describes a set of Excel© macros that may be used to draw a biplot display based on results from principal components analysis, correspondence analysis, canonical discriminant analysis, metric multidimensional scaling, redundancy analysis, canonical correlation analysis or canonical correspondence analysis. The macros allow for a variety of transformations of the data prior to the singular value decomposition and scaling of the markers following the decomposition.